Impact of Workstation Exercise and Ergonomic Exercise on Nursing Population – A Randomized Clinical Trial Research Protocol (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nursing workers represent a significant proportion of the hospital workforce. In recent times, focus is puton increasing efficacy with reducing the concurrent risks in this population. Many researches imply onincluding workplace modifications and various exercises to reduce the number of absenteeism and heightenthe quality in work. As low back ache is the most prevalent, this study targets on determining the effects ofworkstation exercise and ergonomic intervention on it.Purpose -Nursing staff is the base of primary healthcare provision in the Indian background. The mostcommon reason for early retirement, sickness absenteeism, and decline in working population in nurses islow back pain. With proper evidence, the efficacy of workstation activities in nursing staff will mitigate oreliminate this issue in the area of healthcare.Methods: There will be 3 groups, workstation exercise group, ergonomic modification group and a controlgroup each consisting of 40 patients selected from a fixed criterion. They will be graded with a QOL scaleand a pain scale during the start of treatment and after 2 months to compare the results and determine whichtherapy gets better results.Results: Statistical analysis will be done after the study’s completed by use of concise and inferentialtests use Student’sdistribution t test on single and combined analysis, one-way Analysis of Variance (F)ANOVA test and Multiple Comparison: Turkey Test and analytical tools is SPSS24.0 version and GraphPad Prism 6.0 version and p<0.05 is known as value point.Conclusions: Both the ergonomic training and workstation exercises will result in reduction of low backpain with workstation exercises proving more effective. The Publication will be done after conducting thestudy and obtaining the results through the statistical analysis.